Redesigning the European Union's trade policy strategy towards China - Patrick A. Messerlin; Jinghui Wang (European Centre for International Political Economy (ECIPE), 2008)
The European Union's recent trade policy strategy towards China, which focuses on bilateral market access and involves a strong US-style confrontational stance, is ineffective and short-sighted. Today there exists no genuine dialogue between China and the EU on crucial commercial issues. This paper calls for foresightedness in the European Union's policies towards China. It reviews the EU's strategy and proposes concrete policy options that will allow it to more effectively promote its commercial interests in China, by focusing on topics that will draw support from Chinese interests and bring greater economic benefits for both parties. In trade in goods, the paper proposes a "small bargain", involving the granting of market economy status to China in antidumping, in exchange for China's improvement of its WTO tariff schedule implementation. In its "behind-the-border" rules agenda, the proposed EU-China Partnership and Cooperation Agreement could develop a truly "grand bargain" involving a strong reduction of China's highest barriers on inward FDI in services, better access by China to the EU's services markets, joint procedures to address China's Sovereign Wealth Funds' and EU's norms and standards. It would also involve an important scaling down of Europe's requests in issues such as intellectual property rights. More broadly, the EU should review its current trade policy strategy based on bilateral deals and re-focus its trade policy on the WTO. The paper finally argues that EU should also adopt a truly global approach in its trade policy towards China. This means involving not only the United States and Japan, but also successful medium-sized industrial and emerging economies.
Keywords: 330